MODEL PEMBELAJARAN ROLE PLAYING DALAM MATA PELAJARAN AKIDAH AKHLAK KELAS VII DI MTs RAUDLATUL ULUM NGIJO KARANGPLOSO KABUPATEN MALANG - Aneke Ninda Maranita; Jazari Jazari; Kukuh Santoso (VICRATINA, 2022)
The Role Playing learning method aims to enable students to activate students and improve students' understanding of the material provided, especially in the subject of moral aqidah. This application is expected to provide benefits in the teaching and learning process in the classroom. This study uses a qualitative approach by using the type of classroom action research. This survey will be conducted from 20 May 2021 to 20 June 2021. This survey was given to learners. technique for gathering data through observation, test questions and documentation. Data analysis techniques by means of data reduction, data presentation, conclusion drawing, verification/conclusion. The technique of checking the validity of the data is by triangulation. The survey results are as follows. (1) The application of the Role Playing learning model to increase the effectiveness of learning is in accordance with the stages of Role Playing learning. (2) The use of the Role Playing learning model can increase the effectiveness of learning Akidah Akhlak Class 7 Mts Raudlatul Ulum Ngijo, namely from the average value in the first cycle, an average of 71 increased in the second cycle to 84.